Human and Nature Interactions in Kesar Lall’s Folk Tales from Nepal: An Eco-Critical Reading - Budhathoki, Mahendra Kumar (Kaumodaki: Journal of Multidisciplinary Studies, 2024)
Folktales are traditional stories orally handed down to the succeeding generations. They portray the co-existence and collaborations of humans, non-human characters and environments. This study explores the relations and interactions of humans, non-humans and nature in Kesar Lall’s Folk Tales from Nepal: The Origins of Alcohol and other Stories from ecocritical perspective. It has used ecocriticism as a theoretical tool. It is a library and qualitative research. The main finding of this study portrays the association and interactions among humans, non-humans and nature. The attitude of humans exploits the biological and physical environment for the sake of humans. Humans have hostile relations with non-humans like ogre in the natural world. The folktales demonstrate metamorphosis nature of gods and nagas. They portray the death of human beings as the natural process. They have abundant evidences of environments, and they transfer the value of ecological wisdom more to the readers. This study increases the environmental literacy of youths and expands the Nepali folktales to English speaking communities.